2022
DOI: 10.1002/adfm.202111000
|View full text |Cite
|
Sign up to set email alerts
|

Tailorable Polarization‐Dependent Directional Coupling of Surface Plasmons

Abstract: Coupling free‐space light into surface plasmons (SPs) has traditionally faced challenges in arbitrarily controlling the directionality of the SPs with respect to the incident polarization. Recently reported polarization‐dependent directional coupling of SPs using metasurfaces has attracted enormous attention for its promise in developing innovative and on‐demand plasmonic devices. However, further progress has been hampered by the limitation in designating the directional coupling with tailorable polarization‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…In particular, the ability to tailor the wavefront of SPs in the coupling process would greatly simplify the design and fabrication of most integrated plasmonic devices. Several above-mentioned metacouplers could also achieve on-chip wavefront control: for unidirectional metacouplers, López-Tejeira et al demonstrated that by bending the unidirectional metacoupler into a semi-circle shape, coupled SPs can be steered to focus in a very compact region; for gradient phase metacouplers [208] , Xu et al demonstrated that by properly arranging the phase and amplitude of each row of phase gradient meta-atoms, single-order and two-order diffraction of SPs can be achieved [194] ; for multiplexed launching of SPs, Han et al demonstrated polarization-controlled SP focusing and SP Airy beam launching [231] , and Tanemura et al and Wintz et al demonstrated three-level [235] and four-level [236] wavelength-multiplexed focusing of SPs, respectively. In this section, we will introduce more design strategies of SP wavefront control in the coupling process.…”
Section: On-chip Tailoring Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, the ability to tailor the wavefront of SPs in the coupling process would greatly simplify the design and fabrication of most integrated plasmonic devices. Several above-mentioned metacouplers could also achieve on-chip wavefront control: for unidirectional metacouplers, López-Tejeira et al demonstrated that by bending the unidirectional metacoupler into a semi-circle shape, coupled SPs can be steered to focus in a very compact region; for gradient phase metacouplers [208] , Xu et al demonstrated that by properly arranging the phase and amplitude of each row of phase gradient meta-atoms, single-order and two-order diffraction of SPs can be achieved [194] ; for multiplexed launching of SPs, Han et al demonstrated polarization-controlled SP focusing and SP Airy beam launching [231] , and Tanemura et al and Wintz et al demonstrated three-level [235] and four-level [236] wavelength-multiplexed focusing of SPs, respectively. In this section, we will introduce more design strategies of SP wavefront control in the coupling process.…”
Section: On-chip Tailoring Devicesmentioning
confidence: 99%
“…In 2022, Han et al proposed that by utilizing the interference between two pairs of slit resonators [see Fig. 6(j)] with different resonance responses, polarization-controlled unidirectional SP coupling can be expanded to an arbitrary group of orthogonally polarized incidences without affecting efficiency [231] . For each slit-pair, its design strategy is similar to that of Ref.…”
Section: Multiplexed Couplingmentioning
confidence: 99%
“…Due to their compact physical size and robust excitation feature, such dipole sources have been widely adopted as building blocks in constructing functional SP devices, and the ways how to design and utilize them have elicited great research enthusiasm in the last decade [16,17]. Particularly, by incorporating polarization-and/or wavelengthdependences, multiplexed functionalities including directional and asymmetric SP excitations [10,[18][19][20][21][22], plasmonic vortex generations [23][24][25][26], special SP beam launchers [27][28][29][30], and SP metalenses [9,[31][32][33][34][35][36]] have been achieved. Among these demonstrations, the metalenses [9,[31][32][33][34][35][36]] that selectively couple different free-space incidences into SP focusing beams based on wavelength and/or polarization are of extreme importance for on-chip division multiplexing and information routing [37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly, by incorporating polarization-and/or wavelengthdependences, multiplexed functionalities including directional and asymmetric SP excitations [10,[18][19][20][21][22], plasmonic vortex generations [23][24][25][26], special SP beam launchers [27][28][29][30], and SP metalenses [9,[31][32][33][34][35][36]] have been achieved. Among these demonstrations, the metalenses [9,[31][32][33][34][35][36]] that selectively couple different free-space incidences into SP focusing beams based on wavelength and/or polarization are of extreme importance for on-chip division multiplexing and information routing [37][38][39][40][41]. However, the SP metalenses examined thus far intrinsically have limitations in the number of multiplexing channels (mostly two and with only a few reaching four) and in the relative directionality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation